2015
DOI: 10.1183/13993003.00099-2015
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumour standardised uptake value is prognostic in nonsmall cell lung cancer: a multivariate pooled analysis of individual data

Abstract: 18 F-fluoro-2-deoxy-D-glucose positron emission tomography (PET) complements conventional imaging for diagnosing and staging lung cancer. Two literature-based meta-analyses suggest that maximum standardised uptake value (SUVmax) on PET has univariate prognostic value in nonsmall cell lung cancer (NSCLC). We analysed individual data pooled from 12 studies to assess the independent prognostic value of binary SUVmax for overall survival.After searching the published literature and identifying unpublished data, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 47 publications
0
26
3
2
Order By: Relevance
“…T-stage, N-stage, complexity of surgical procedure and overall survival) [13]. A multivariate pooled analysis of survival in 1526 NSCLC patients confirmed SUVmax as independent prognostic factor ''in adenocarcinoma and squamous cell carcinoma'' [14], and similar conclusions were reported by another meta-analysis [15].…”
Section: Discussionmentioning
confidence: 73%
“…T-stage, N-stage, complexity of surgical procedure and overall survival) [13]. A multivariate pooled analysis of survival in 1526 NSCLC patients confirmed SUVmax as independent prognostic factor ''in adenocarcinoma and squamous cell carcinoma'' [14], and similar conclusions were reported by another meta-analysis [15].…”
Section: Discussionmentioning
confidence: 73%
“…The evaluation of SUV is intuitive and convenient, but whether SUVmax provides additional prognostic value in addition to the TNM stage remains to be explored [12,13,21]. Previous studies showed that higher SUVmax was associated with worse overall survival, but these studies were mostly based on early stage lung cancer [4,6,18,22],and results have been con icting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a high sensitivity,speci city,and accuracy of PET/CT for diagnosis,staging [2][3][4]12],post-therapy assessment, and outcome prediction [2,4,7,8,10,11,[13][14][15][16][17][18][19] as well as its utility as an accurate and non-invasive modality in clinical practice. However, the methods in these studies differ and their conclusions are not completely consistent [12,20,21]. Furthermore, the utility of SUV for predicting survival in advanced NSCLC requires further study.…”
Section: Introductionmentioning
confidence: 99%
“…The largest study (311 patients, UICC stage I-III) further showed that ASP, with an optimal cut-off of > 19.5%, could identify patients with UICC stage II treated by surgery and adjuvant chemotherapy with high ASP and reduced PFS (median, 11 months vs. not reached) and OS (22 months vs. not reached) (15). ASP was superior for survival prediction compared to primary tumor's maximum standardized uptake value (SUVmax) and MTV, two other previously proposed and common PET parameters (8,9,16,17).…”
Section: Introductionmentioning
confidence: 96%